Molecular epidemiology of serotype 19A Streptococcus pneumoniae among invasive isolates from Alaska, 1986–2010 - Rudolph, Karen; Bruce, M.G.; Bulkow, L.; Zulz, T.; Reasonover, A.; Harker-Jones, M.; Hurlburt, D.; Hennessy, T.W.
Background After the introduction of the 7-valent pneumococcal conjugate vaccine (PCV7) in Alaska, the incidence of invasive pneumococcal disease (IPD) due to non-vaccine serotypes, particularly serotype 19A, increased. The aim of this study was to describe the molecular epidemiology of IPD due to serotype 19A in Alaska. Methods IPD data were collected from 1986 to 2010 through population-based laboratory surveillance. Isolates were serotyped by the Quellung reaction and MICs determined by broth microdilution. Genotypes were assessed by multilocus sequence typing. Results Among 3,294 cases of laboratory-confirmed IPD, 2,926 (89%) isolates were available for serotyping, of which 233 (8%) were serotype 19A. Across all ages, the proportion of IPD caused by serotype 19A increased from 3.5% (63/1823) pre-PCV7 (1986–2000) to 15.4% (170/1103) post-PCV7 (2001–2010) (p<0.001); among children <5 years of age, the proportion increased from 5.0% (39/776) to 33.0% (76/230) (p<0.001). The annual incidence rate of IPD due to serotype 19A (all ages) increased from 0.73 cases pre-PCV7 to 2.56 cases/100,000 persons post-PCV7 (p<0.001); rates among children <5 years of age increased from 4.84 cases to 14.1 cases/100,000 persons (p<0.001). Among all IPD isolates with reduced susceptibility to penicillin, 17.8% (32/180) were serotype 19A pre-PCV7 and 64% (121/189) were serotype 19A post-PCV7 (p<0.001). Eighteen different sequence types (STs) were identified; ST199 or single locus variants of ST199 (n=150) and ST172 (n=59) accounted for the majority of isolates. Multidrug-resistant isolates were clustered in ST199 and ST320. Conclusion While PCV13 should significantly reduce the burden of disease due to 19A, these data highlight the need to continue surveillance for IPD to monitor the effects of vaccination on the expansion and emergence of non-PCV strains.